Facilitating transition to medical school for undergraduate students through medical student-led case-based learning workshops within a combined Bachelor of Science and Doctor of Medicine program - Chauhan, Sneha; Martin, Luke; Senthil, Vani; Cheema, Herjot; D'Eon, Marcel (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Implication StatementWe developed and implemented an interdisciplinary workshop to increase confidence amongst pre-medical students when transitioning to medical school. We were inspired by the collaborative small-group Case Based Learning (CBL) sessions from the pre-clerkship curriculum at our medical school. By involving medical student volunteers as group facilitators, this workshop was a feasible and sustainable addition to medical school preparation for undergraduate students enrolled in an integrated medical pathway. Furthermore, our model suggests advantages for similar programs at other institutions, providing early exposure to clinical expectations.